Impacts of Rainfall Variability and Urban Sprawl on the Environment and the Population Well-being at Ouakam Commune, Dakar, Senegal - Mamadou Lamine Ndiaye; El Hadji Amath Diodio Ndiaye; Vieux Boukhaly Traore; Amadou Tahirou Diaw; Aboubacker Chedikh Beye (Archives of Current Research International, 2016)
In many Southern African countries, climate change observed these last years, had serious consequences on the environment and the well-being of urban populations. This study aims to analyze the consequences due to rainfall variability and urban dynamics in the Commune of Ouakam. Analysis of rainfall variability based on the calculation of the reduced centered variable allowing identifying surplus and deficit years. Urban dynamics analysis based on land use maps obtained through visual interpretation and post-classification approach to identify the types of change. A field survey was conducted among households and health facilities to gather further information on the issue relating to parasitic and respiratory diseases caused by the floods and the dynamics of land use. The results show a return of rainfall during the past two decades causing flooding in places. The dynamics of land use is manifested by a conversion of crops areas into habitation areas. This led to the development of irregular habitat from 2% in 1942 to 20% in 2014, public health problems with the proliferation of parasitic and endemic diseases and floods with their multiple damage in terms socioeconomic. This study is for local authorities, an important tool in understanding of the major difficulties the Ouakam commune faces Therefore, solutions can and must be considered immediately.